INHERITANCE OF QUANTITATIVE TRAITS IN THE F1 GENERATION OF COTTON (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In this article, the inheritance of quantitative traits in F1 hybrid combinations exhibited various patterns, including absence of dominance, intermediate, complete, and overdominance. The inheritance of the abovementioned quantitative traits indicated that they possess a polygenic nature.
Keywords: Cotton, precocity, box weight, productivity, fiber yield, weight of 1000 pieces of seeds, fiber quality, micronaire, breeding, seed production, saline soil, line, variety.